Sister Boniface mysteries. Season 4 [videorecording (DVD)] - Tindall, Jude (BBC, 2025)
The nun who is the police's secret weapon is back. Crime solving is her habit! The wine-making, moped-riding nun investigates more ugly deeds in beautiful surroundings. It's the mid-1960s in the quaint Cotswold village of Great Slaughter, but strange things are afoot. A killer scarecrow stalks the streets, all the women call a general strike and the police embark on something called "team building". Sister Boniface is looking forward to a wholesome weekend away with the sisters, only to be confronted with yet another murder.